EFEKTIVITAS KINERJA SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PEDAGANG KAKI LIMA (STUDI KASUS PASAR KODIM KOTA PEKANBARU) - Bonni Edwandar; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
problem of street vendors (PKL) Air urban land is still the dilemma is still not complete. No exception to the cities in Riau in Pekanbaru, especially street vendors who often gets the spotlight. Curbing the sake of policing is often done by the municipal police as the party who share responsibility in realizing the public order in the area, but the street vendors still survive today.This study aims to determine the effectiveness of performance in the Civil Service Police Unit Control of Street Vendors in the Market District Military Command Pekanbaru. In addition this study aims to identify and analyze factors that hinder the effectiveness of performance in the Civil Service Police Unit Control of Street Vendors in the Market District Military Command Pekanbaru. Sources of data used in this research is using qualitative and descriptive research conducted in the Office of Civil Service Police Unit of Pekanbaru.Results of this research is that productivity performance in curbing municipal police organization Street Vendors in the Market District Military Command Pekanbaru City ineffective. Quality of service in controlling street vendors in the Market District Military Command Pekanbaru City insufficient, Responsiveness municipal police in controlling street vendors in the Market District Military Command Pekanbaru City not in accordance with the needs of the Merchant Responsibility municipal police Pekanbaru City law enforcement or sanction is very low, and Accountability Satpol PP Pekanbaru in curbing activities of street vendors in the Market District Military Command Pekanbaru City is very low. Barriers experienced by municipal police in controlling street vendors in the Market District Military Command Pekanbaru City ie street vendors in the Market District Military Command still had the awareness is very low, the shortage of personnel municipal police who are members of an audit, and no other place that can be used to relocate Street vendors.Keywords: Effectiveness Performance, Civil Service Police Unit, Street Vendors